2020
DOI: 10.1007/s12035-020-02070-6
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Involvements of SARS-CoV2 Infection

Abstract: COVID-19 is a pandemic viral infection caused by a novel coronavirus, SARS-CoV2, which is a global concern of the twentyfirst century for its rapid spreading in a short period. Apart from its known acute respiratory involvements, the CNS manifestations of COVID-19 are common. These neurological symptoms are diverse and could range from mild nonspecific or specific symptoms such as the loss of various sensory perceptions, the worrying autoimmune Guillain-Barré syndrome, to the lifethreatening acute disseminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 60 publications
(89 reference statements)
0
40
0
Order By: Relevance
“…There is no definitive evidence that SARS-CoV-2 is neuropathogenic [ 217 ]. Despite many inconsistencies, research has demonstrated a connection between SARS-CoV-2 infection and neurological disorders, including Alzheimer’s disease [ 218 , 219 , 220 , 221 ]. Furthermore, a postinfectious inflammatory disease known as a multisystem inflammatory syndrome in children (MIS-C) has emerged as a major COVID-19-related medical condition [ 222 ].…”
Section: Inflammatory Cytokines and Multiple Organ Damagementioning
confidence: 99%
“…There is no definitive evidence that SARS-CoV-2 is neuropathogenic [ 217 ]. Despite many inconsistencies, research has demonstrated a connection between SARS-CoV-2 infection and neurological disorders, including Alzheimer’s disease [ 218 , 219 , 220 , 221 ]. Furthermore, a postinfectious inflammatory disease known as a multisystem inflammatory syndrome in children (MIS-C) has emerged as a major COVID-19-related medical condition [ 222 ].…”
Section: Inflammatory Cytokines and Multiple Organ Damagementioning
confidence: 99%
“…Her otherwise intact orientation and cognitive capacities do not suggest delirium, dementia, or another neurocognitive disorder resulting from SARS-CoV-2 infection. 12 , 13 There are no accompanying features of psychosis, such as distinct hallucinations, delusions, or thought disorder, that would suggest new development of a primary psychotic illness.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…SARS-CoV-2 is a respiratory virus, but prior reports suggest that it may also disseminate to the brain via the olfactory mucosa (Cantuti-Castelvetri et al, 2020;Meinhardt et al, 2021;Song et al, 2021). Post-mortem analyses of COVID-19 patients have shown the presence of SARS-CoV-2 in the brain (Gasmi et al, 2021;Kumari et al, 2021;Meinhardt et al, 2021;Song et al, 2021).…”
Section: Introductionmentioning
confidence: 99%